2021
DOI: 10.1101/2021.04.30.442163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disease-linked TDP-43 hyperphosphorylation suppresses TDP-43 condensation and aggregation

Abstract: Post-translational modifications (PTMs) have emerged as key modulators of protein phase separation and have been linked to protein aggregation in neurodegenerative disorders. The major aggregating protein in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), the RNA-binding protein TDP-43, is hyperphosphorylated in disease on several C-terminal serine residues, which is generally believed to promote TDP-43 aggregation. Here, we show that hyperphosphorylation by Casein kinase 1δ or C-termina… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 78 publications
2
12
1
Order By: Relevance
“…In FTLD‐TDP‐C, pS403/404 was consistently a prerequisite for pS409/410, leading to a higher total percentage of bi‐phosphorylated protein over time. The increased hyperphosphorylation and slower fibril growth rate we observed for FTLD‐TDP‐C is consistent with studies showing that phosphorylation increases solubility and decreased protein accumulation (preprint: Silva et al , 2021 ). As phosphorylation may affect the ultimate atomic structure of TDP‐43 fibrils (Li et al , 2021 ), our results suggest that differential phosphorylation could mediate the formation of specific fibril strains to direct disease‐subtype specificity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In FTLD‐TDP‐C, pS403/404 was consistently a prerequisite for pS409/410, leading to a higher total percentage of bi‐phosphorylated protein over time. The increased hyperphosphorylation and slower fibril growth rate we observed for FTLD‐TDP‐C is consistent with studies showing that phosphorylation increases solubility and decreased protein accumulation (preprint: Silva et al , 2021 ). As phosphorylation may affect the ultimate atomic structure of TDP‐43 fibrils (Li et al , 2021 ), our results suggest that differential phosphorylation could mediate the formation of specific fibril strains to direct disease‐subtype specificity.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies support the notion that serine phosphorylation within the low complexity region of TDP‐43 may inhibit protein aggregation in vitro and in cells. Indeed, cryo‐EM studies showed that the core fibril structure would be significantly disrupted by phosphorylation at key residues in that same domain (Li et al , 2021 ), whereas an independent study showed that TDP‐43 phosphorylation within the C‐terminal region increases solubility and counteracts protein accumulation in cells (preprint: Silva et al , 2021 ). In combination with our results pointing to fibril structure polymorphism between the subtypes, these data suggest that the phosphorylation state of TDP‐43 could play a key role in the mechanism underlying the disease‐specific subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is mounting evidence that single point mutations can strongly influence TDP-43’s functional properties, conceivable through altering LLPS propensities. Furthermore, a recent study investigating the impact of phosphomimic substitutions in TDP-43 (serine to aspartic acid) reported that hyperphosphorylation affected LLPS and might be protective under specific circumstances (Silva et al, 2021). The authors demonstrated that an increased number of phosphomimic mutations (12D compared to 5D and WT-TDP-43) reduced FRAP recovery rates, increased BMCs dynamics, and reduced TDP-43 aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, impaired shuttling is likely central to the pathogenesis of sALS. Following the protein's permanent sequestration from the nucleus into the cytoplasm, pathological TDP-43 assemblies (oligomers) could serve as 'scaffolds' for the development of inclusion bodies (aggregates) that undergo posttranslational modifications, for example, C-terminal fragmentation, abnormal phosphorylation at multiple sites, ubiquitination, and aceylation [3][4][5]94,[117][118][119][120][121][122]; but see [123]). Particularly the regions of the C-terminal have been shown to be aggregation-prone [123][124][125][126][127].…”
Section: Tdp-43 Nucleocytoplasmic Trafficking Mislocalization In Neur...mentioning
confidence: 99%